2015
DOI: 10.1152/ajpregu.00366.2014
|View full text |Cite
|
Sign up to set email alerts
|

Brain ACE2 overexpression reduces DOCA-salt hypertension independently of endoplasmic reticulum stress

Abstract: -Endoplasmic reticulum (ER) stress was previously reported to contribute to neurogenic hypertension while neuronal angiotensin-converting enzyme type 2 (ACE2) overexpression blunts the disease. To assess which brain regions are important for ACE2 beneficial effects and the contribution of ER stress to neurogenic hypertension, we first used transgenic mice harboring a floxed neuronal hACE2 transgene (SL) and tested the impact of hACE2 knockdown in the subfornical organ (SFO) and paraventricular nucleus (PVN) on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 39 publications
2
26
1
Order By: Relevance
“…Ang-(1–7) has an effect opposite that of Ang II in that it stimulates nitric oxide (NO) release, improves baroreceptor reflexes sensitivity, and promotes vasodilation (Rabelo, Alenina, & Bader, 2011). Consistent with this, overexpression of human ACE2 in neurons or specifically in the RVLM or SFO causes a reduction in BP in Ang II-induced hypertensive mice and spontaneously hypertensive rats (SHR) (Feng, et al, 2008; Xia, et al, 2015; Yamazato, Yamazato, Sun, Diez-Freire, & Raizada, 2007). AGT in the brain is synthesized and secreted from astroglial cells (Campbell, Bouhnik, Menard, & Corvol, 1984; Deschepper, Bouhnik, & Ganong, 1986; Sernia & Mowchanuk, 1983) and neurons (G.…”
Section: The Prr Is a Master Regulator Of Bp In The Brain Rassupporting
confidence: 54%
“…Ang-(1–7) has an effect opposite that of Ang II in that it stimulates nitric oxide (NO) release, improves baroreceptor reflexes sensitivity, and promotes vasodilation (Rabelo, Alenina, & Bader, 2011). Consistent with this, overexpression of human ACE2 in neurons or specifically in the RVLM or SFO causes a reduction in BP in Ang II-induced hypertensive mice and spontaneously hypertensive rats (SHR) (Feng, et al, 2008; Xia, et al, 2015; Yamazato, Yamazato, Sun, Diez-Freire, & Raizada, 2007). AGT in the brain is synthesized and secreted from astroglial cells (Campbell, Bouhnik, Menard, & Corvol, 1984; Deschepper, Bouhnik, & Ganong, 1986; Sernia & Mowchanuk, 1983) and neurons (G.…”
Section: The Prr Is a Master Regulator Of Bp In The Brain Rassupporting
confidence: 54%
“…Whereas, the absence of an effect on blood pressure is consistent with a previous report observing no changes in DOCA-salt induced blood pressure in response to TUDCA 42 , it stands in contrast to two other studies where relief of ER stress prevented the hypertensive response in Ang-II 14 and reduced blood pressure in the spontaneously hypertensive rat. 43 Assuming there are no technical limitations in both DOCA-salt studies, these results have two main implications.…”
Section: Discussionsupporting
confidence: 91%
“…However, it was recently reported that increased expression of the mRNAs encoding several ER stress biomarkers (s-XBP, ATF4, GRP78 [also known as BiP] and CHOP) was evident in the SFO and to a lesser extent the paraventricular nucleus (PVN) of DOCA-salt-treated mice. 42 However, unlike their study which surprisingly concluded that ER stress does not occur in the SFO in response to DOCA-salt, our identification of increased CHOP protein in the SFO (and SON) concomitant with ultrastructural changes consistent with ER stress, and decreased saline intake in response to SFO-targeted delivery of AdGRP78 provide compelling evidence for the induction of ER stress in the SFO in response to DOCA-salt.…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…ERS mediated Ang II-dependent hypertension in SFO through nuclear factor (NF)-кB activation [115] . ERS also contributed to neurogenic hypertension [116] . Severe hypertension caused neuronal injury through neuronal ERS and apoptosis [117] .…”
Section: Endoplasmic Reticulum Stress Regulates Cardiovascular Physiomentioning
confidence: 99%